Sleep duration and blood pressure in children: Analysis of the pan‐European IDEFICS cohort. Issue 5 (20th March 2019) - Sparano, Sonia; Lauria, Fabio; Ahrens, Wolfgang; Fraterman, Arno; Thumann, Barbara; Iacoviello, Licia; Marild, Staffan; Michels, Nathalie; Molnar, Denes; Moreno, Luis Alberto; Tornaritis, Michael; Veidebaum, Toomas; et al.
Abstract : The present study aims to examine the cross‐sectional and longitudinal association between self‐reported nocturnal sleep duration, blood pressure, and hypertension in European children, aged 2‐9.9 years, participating in the IDEFICS project. Blood pressure (BP) and the main anthropometric indices were measured according to standardized procedures. Childhood elevated BP and hypertension were defined according to the European Society of Hypertension Guidelines for children and adolescents. Parents reported lifestyle and socio‐demographic data. Nocturnal sleep duration was assessed as part of a parental 24‐h recall and categorized as follows: (a) ≤9 hours/night; (b) >9 hours to ≤10 hours/night; (c) >10 hours to ≤11 hours/night; and (d) >11 hours/night. A complete set of variables included in the present analysis was provided by 7974 participants (boys/girls = 4049/3925) at the baseline survey (T0). Of them, 5656 were re‐examined 2 years later at follow‐up (T1). Children reporting shorter sleep duration at T0 had significantly higher BP values ( P for trend < 0.001) compared to those who slept more. Prospective analyses showed that shorter sleep duration at baseline predicted, over the 2‐year follow‐up, higher increases in systolic blood pressure and diastolic blood pressure, after adjustment for age, sex, country of origin, BMI z ‐score, parental education, physical activity, screen time, and T0 value of the examined outcome variables ( P for trend < 0.001). Our findings reveal that shorter sleep duration is associated with higher BP in childhood, suggesting that sleep may be a potential risk factor for hypertension later in life.